Character Development through Dance Learning in an Early Childhood Setting - Rakimahwati, Rakimahwati (Indonesian Journal of Early Childhood Education Studies, 2014)
The problems happening to school-age children have encouraged teachers’ strong efforts to overcome them. Character based education becomes one of the solutions to handle those problems. Character based education should have begun since early ages. This research investigates how to build children’s character in their early ages through the activities of learning dance art. This is a descriptive research with a qualitative approach. The date was collected through interviews, recordings, and photo or video shooting. The reliability and the validity of the data were done by verifying and cross-checking the data. In addition, the technique of data analysis was adopted from Spradley’s (1997) steps in which the data were validated based on their credibility, transferability, dependability, and confirmability.The findings show that character-based education for early childhood through dance art learning is effective. The learning process can inculcate the character values such as discipline, honesty, responsibility, religious, patriotism, and environmental care.How to citeRakimahwati, R. (2014). Character Development through Dance Learning in an Early Childhood Setting. Indonesian Journal Of Early Childhood Education Studies, 3(2), 102-107. doi:10.15294/ijeces.v3i2.9490